2019
DOI: 10.4314/mejs.v11i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Recharge Estimation Using WetSpass Modeling in Upper Bilate Catchment, Southern Ethiopia

Abstract: The study area, upper Bilate catchment, is strongly dependent on groundwater like other rural catchments in the country. The main objective of this work is to quantify the amount of groundwater recharge in upper Bilate catchment. Recharge was estimated using physically based distributed recharge model called WetSpass. As input to the model precipitation, potential evapotranspiration, temperature and wind speed were estimated using data collected from meteorological stations located within the catchment and nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…12) shows that the calculated groundwater recharge ranges from 0 to 37 mm/month with a spatial average of 10.10 mm/month. This result is 9.8% of the monthly average rainfall of the study area and this estimated groundwater recharge confirms the findings of Dereje and Nedaw (2019) for upper Bilate catchment, showing that the average groundwater recharge is 9.4% of the annual precipitation. The influence of rainfall distribution in the catchment is significantly noticeable in the spatial distribution of groundwater recharge.…”
Section: Groundwater Rechargesupporting
confidence: 90%
“…12) shows that the calculated groundwater recharge ranges from 0 to 37 mm/month with a spatial average of 10.10 mm/month. This result is 9.8% of the monthly average rainfall of the study area and this estimated groundwater recharge confirms the findings of Dereje and Nedaw (2019) for upper Bilate catchment, showing that the average groundwater recharge is 9.4% of the annual precipitation. The influence of rainfall distribution in the catchment is significantly noticeable in the spatial distribution of groundwater recharge.…”
Section: Groundwater Rechargesupporting
confidence: 90%
“…In the Birki Watershed, Eastern Tigray, Northern Ethiopia, [30] get 85.5 percent of yearly precipitation. [31] simulated 69.8% of annual precipitation in the Upper Bilate Catchment, Southern Ethiopia, and [26] reported 81 percent in the Illala Catchment, Northern Ethiopia. As a result, evapotranspiration eliminates the bulk of annual precipitation [32,33].…”
Section: Wetspass Model Simulationmentioning
confidence: 99%
“…erefore, the study concluded that precipitation and LULC are the main driving factors of actual evapotranspiration in the basin. e previous investigation conducted by Dereje and Nedaw [14] and Molla et al [73] have estimated groundwater recharge, EVT, and surface runoff using the WetSpass hydrological model in upper Bilate watershed and Abaya-Chamo basin.…”
Section: Winter Surface Runoffmentioning
confidence: 99%
“…A few researchers [74] have revealed that the settlement and built-up areas have a tendency to generate a high volume of surface runoff within the region because they have substantially smaller amount vegetative area. erefore, the study conducted by Dereje and Nedaw [14], and Molla et al [73] have been ignored by the potential contributions of settlement and built-up area on hydrological processes during their evaluation, although the dynamics of urbanization is evidently ongoing in the basin. During the study, the potential impacts of settlement and the built-up area on surface and subsurface water were investigated, and the determined results experienced that surface runoff has been evidently affected by the degree of settlement and modification of urbanization in the Bilate basin.…”
Section: Winter Surface Runoffmentioning
confidence: 99%
See 1 more Smart Citation